2016
DOI: 10.1080/13621718.2015.1125407
|View full text |Cite
|
Sign up to set email alerts
|

Dissimilar Al/steel friction stir spot welding: To penetrate into the lower steel sheet or not?

Abstract: There has always been a question about which condition results in superior mechanical properties in friction stir spot welds: (i) when the tool tip penetrates into the lower sheet or (ii) when the tool tip does not touch it. Given the question, the effects of the tool penetration depth were investigated on the microstructure and mechanical behaviour of dissimilar Al-5083/St-12 joints produced by friction stir spot welding (FSSW). Two different processes named as non-penetrating and penetrating FSSW were used. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…The strength of the joints depends not only on the metallurgical bonding, but also the formation of hook. The latter acts as a mechanical interlock and contributes to increasing joint strength . In the joints with relatively lower Q applied (eg, Joint 2), which is associated with weak metallurgical bonding (between thin IMC layer and 6061Al) and small mechanical interlock, crack prefers to propagate along the interface of the 6061Al/IMC layer (Figure A,B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The strength of the joints depends not only on the metallurgical bonding, but also the formation of hook. The latter acts as a mechanical interlock and contributes to increasing joint strength . In the joints with relatively lower Q applied (eg, Joint 2), which is associated with weak metallurgical bonding (between thin IMC layer and 6061Al) and small mechanical interlock, crack prefers to propagate along the interface of the 6061Al/IMC layer (Figure A,B).…”
Section: Resultsmentioning
confidence: 99%
“…The latter acts as a mechanical interlock and contributes to increasing joint strength. 3,7 In the joints with relatively lower Q applied (eg, Joint 2), which is associated with weak metallurgical bonding (between thin IMC layer and 6061Al) and small mechanical interlock, crack prefers to propagate along the interface of the 6061Al/IMC layer ( Figure 10A,B). By increasing Q applied to relatively moderate value (eg, Joint 4), the bonding strength increased due to activation of elemental diffusion across the interface (ie, strong metallurgical bonding) and increasing hook area (ie, higher mechanical interlocking); these deviated the failure path to the Al side near the joint interface ( Figure 10C,D).…”
Section: Failure Mechanisms During Tensile-shear Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Pourali et al found that mechanical connections are the main connection methods of aluminum/steel composite plate under the condition of low welding speed [14]. During explosive welding, the energies of explosion flow cause some of the steel and aluminum soften or even melt, mix and finally form the morphologies of hooks or vortexes at the interface [16,17]. Meanwhile, defects such as steel cuttings and microcracks caused by explosion weaken the strength of composite.…”
Section: Introductionmentioning
confidence: 99%
“…In the second part, tunnel defects are usually found in the composite plate after the single-pass FSP [11,15,16,28]. Kima investigated different tool plunge downforces of FSW for ADC12 aluminum die casting alloy.…”
Section: Introductionmentioning
confidence: 99%